Correction to: An Ex vivo Analysis of Apical Transportation in Root Canals Prepared with BT Race Rotary and Hand K-Flexofile by Cone Beam Computed Tomography - Abbas Mesgarani; Azadeh Zakariaie; Azam Haddadi Kohsar; Sina Haghanifar3; Jamshid Yazdani Charati; Arman Ebrahimi (Journal of Mazandaran University of Medical Sciences, 2020)
Correction to: An Ex vivo Analysis of Apical Transportation in Root Canals Prepared with BT Race Rotary and Hand K-Flexofile by Cone Beam Computed Tomography